2021
DOI: 10.1186/s13006-021-00377-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of coronavirus outbreak on breastfeeding guidelines among Brazilian hospitals and maternity services: a cross-sectional study

Abstract: Background The World Health Organization recognizes exclusive breastfeeding a safe source of nutrition available for children in most humanitarian emergencies, as in the current pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Despite the Brazilian national guideline protecting breastfeeding practices, there are many concerns about protecting infants from their infected mothers. This study aimed to analyze how the Brazilian hospitals and maternity services pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
1
19
0
2
Order By: Relevance
“…The risk of vertical transmission of SARS-CoV-2 through the breastmilk is low ( 33 , 35 , 105 ). Therefore, recommendations for pregnant COVID-19 patients have been rapidly shifting with various waves of the pandemic, but in general, World Health Organization ( 90 ), United Nations International Children’s Emergency Fund ( 106 ), and most countries ( 107 , 108 ) support mothers with COVID-19 to contact and breastfeed their newborns and infants following the necessary hygiene rules, including disinfection with alcohol, wearing face masks, and obtaining written informed consent from parents ( 109 ).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of vertical transmission of SARS-CoV-2 through the breastmilk is low ( 33 , 35 , 105 ). Therefore, recommendations for pregnant COVID-19 patients have been rapidly shifting with various waves of the pandemic, but in general, World Health Organization ( 90 ), United Nations International Children’s Emergency Fund ( 106 ), and most countries ( 107 , 108 ) support mothers with COVID-19 to contact and breastfeed their newborns and infants following the necessary hygiene rules, including disinfection with alcohol, wearing face masks, and obtaining written informed consent from parents ( 109 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, many hospitals have suspended human milk banking services due to the reduced number of personnel, resulting from imposed quarantine or isolation [ 67 ]. In Brazil [ 91 ], most of the medical centers did not accept milk donation due to fear of SARS-CoV-2 infection (23 out of 24, 95.8% of reviewed hospitals). Therefore, as it was reported by the Collaborative Network of Milk Banks and Associations, the significant decrease in human milk donation rates was globally observed in the time of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In 19% (7 papers) it was directly indicated that, regarding SSC, pre-pandemic recommendations should not be changed and routine care should be provided [18,42,47,69,82,86,87]. Recommendations against SSC were found in 27% of the papers addressing this issue (15 papers) [25,26,[28][29][30]37,48,53,61,62,64,68,89,90], including 1 paper in which different kinds of Brazilian recommendations, mostly prohibiting SSC, were recalled and discussed due to being controversial and potentially negatively impacting breastfeeding success, but the authors did not formulate their own recommendations [91]. Half of the recommendations (7 studies) among those against SSC were published in the second and third quarters of 2020 [25,26,37,61,62,64,68].…”
Section: Skin-to-skin Contact and Kangaroo Care Interventionmentioning
confidence: 99%
“…These restrictions have a negative effect on mother's mood, self-esteem, self-confidence and confidence in their abilities related to their infant's care. Standard precautions (such as hand hygiene, use of medical mask, routine disinfection) applied by mothers with suspected, or confirmed COVID-19, who must take care of their infants by themselves, may impose psychological demands on new mothers and may complicate the early mother-infant relationship ( 51 56 ).…”
Section: Possible Factors That May Have Affected Negatively Perinatal...mentioning
confidence: 99%
“…However, the absence of recommendations on breastfeeding support and lack of support has led to reduced compliance to the recommendations of main scientific institutions suggesting breastfeeding initiation. This may has affected adversely both maternal mental health and the rate of breastfeeding ( 50 , 51 , 109 ). However, mothers experience breastfeeding heterogeneously since 41.8% felt that breastfeeding was protected due to the lockdown but 27% of mothers reported a negative impact of lockdown upon their breastfeeding experience.…”
Section: Possible Factors That May Have Affected Negatively Perinatal...mentioning
confidence: 99%